(3CKQ GdeTQhYGJ GdUZjQI aj JfejI GdeQCI GdQjajI GdadSWjfjI (B: s (3OQGSI ejOGfjI aj TeGd bWGY ZRI (B/ s - (3eMeO SdjeGf UGdM fThGfs; (3MSf CMeO GdNhdj (B: s ((3GdbGgQI (B: s (3eMeO SdjeGf UGdM fThGf (B: s, 2015)
(3gOaJ gPg GdOQGSI Gdi GdcTa Yf GdCKQ GdMbjbj ddeTQhYGJ GdUZjQI aj JfejI GdeQCI GdQjajI (B: (3h Cf GdOQGSI JgOa ddhUhd Gdi LedI ef GdCgOGa h efgG (B: (3GdJYQa Ydi GdeDSSGJ GdJj JOYe JfejI GdeQCI GdQjajI h GdJYQa Ydi CgejI GdeTQhYGJ GdUZjQI ddeQCI GdQjajI h JfejJgG h GdJYQa Ydi GdeTcdGJ GdJj JYhb JfejI GdeQCI GdQjajI h GdJYQa Ydi GdeYhbGJ GdJj JhGLg GdeDSSGJ aj OYe GdeQCI GdQjajI h GdJYQa Ydi GdeYhbGJ GdeLJeYjI h fXQI GdeLJeY ef UGMHGJ GdeTGQjY GdUZjQI (B: (3h cPdc GdYed Ydi JbOje EbJQGMGJ h JhUjGJ ceSGgeI aj hVY JUhQ eJcGed dJfejI GdeQCI GdQjajI EbJUGOjB h GLJeGYjBs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdOhd GdYQHjI (B- ((3GdefXeI GdYQHjI ddJQHjI h GdKbGaI h GdYdhe(B) - (3eYgO GdHMhK h GdOQGSGJ GdYQHjI (B- (3bSe GdOQGSGJ GdGLJeGYjIs
Keywords: (3GdeQCI GdQjajI GdadSWjfjIs; (3GdeTQhYGJ GdUZjQI s; (3TeGd bWGY ZRIs